2017
DOI: 10.4238/gmr16019515
|View full text |Cite
|
Sign up to set email alerts
|

Leptin (rs7799039) and solute carrier family 30 zinc transporter (rs13266634) polymorphisms in Euro-Brazilian pregnant women with gestational diabetes

Abstract: ABSTRACT. Leptin (LEP), a protein that plays a fundamental role in the metabolism of energy reserves, and the solute carrier family 30 A8 zinc transporter (SLC30A8) have been consistently associated with diabetes. Women with gestational diabetes are at moderate risk of developing diabetes type 1 and 2 after pregnancy, in addition to complications to the fetus. We investigated the association of the polymorphisms rs7799039 (LEP) and rs13266634 (SLC30A8) in a case-control study in Euro-Brazilians with gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…It was found that the minor allele frequency of LEP rs7799039 A>G polymorphism might alter sharply among different populations (0.201 [Chinese] vs 0.597 [Caucasians]). 28 Recently, Romanowski et al reported that LEP rs2167270 G>A polymorphism increased the risk of posttransplant diabetes mellitus. 29 LEP rs2167270 G>A is located in 5′-untranslated region and may influence the translation process of LEP mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the minor allele frequency of LEP rs7799039 A>G polymorphism might alter sharply among different populations (0.201 [Chinese] vs 0.597 [Caucasians]). 28 Recently, Romanowski et al reported that LEP rs2167270 G>A polymorphism increased the risk of posttransplant diabetes mellitus. 29 LEP rs2167270 G>A is located in 5′-untranslated region and may influence the translation process of LEP mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies have identified more than 100 independent SNPS associated with T2DM regulation and risk [ 32 ]. Several gene polymorphisms of leptin have been reported to be associated with T2DM [ 2 , 33 ]. For example, the leptin (LEP) G2548A polymorphism has been associated with increased leptin production and plasma secretion from adipocytes [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has become a major public problem around the world [ 1 ], with the numbers increasing from 108 million in 1980 to 422 million in 2014 [ 2 ], and the number of people with diabetes is expected to increase to 592 million by 2035 [ 3 ]. Type 2 diabetes mellitus (T2DM) is the most prevalent form of diabetes mellitus (DM), accounting for about 90-95% of the total number of DM cases worldwide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rs1326634 variant in SLC30A8 has recently gained much interest in GDM risk. In the present meta-analysis, a total of six studies (Cho et al, 2009;Dereke et al, 2012;Khan et al, 2019;Lauenborg et al, 2009;Teleginski et al,,, 2017) having 3861 controls and 1946 GDM cases were analyzed. Overall-effect analysis showed the signi cantly (p<0.00001) increased susceptibility with increased GDM risk only in the dominant (OR-1.91) and heterozygote model (OR-2.90), while in the allelic models, there was signi cantly (p<0.05) decreased susceptibility (OR-0.76) associated with GDM risk (Fig.…”
Section: Zinc Transporter 8 (Slc30a8)mentioning
confidence: 99%